2022
DOI: 10.1021/acs.accounts.1c00657
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Double-Helical Metallopolymers

Abstract: Conspectus Metal-containing polymers, or metallopolymers, have diverse applications in the fields of sensors, catalysis, information storage, optoelectronics, and neuromorphic computing, among other areas. The approach of metal-templated subcomponent self-assembly using dynamic covalent linkages allows complex architectures to be formed with relative synthetic ease. The dynamic nature of the linkages between subunits in these systems facilitates error checking during the assembly process and also provides a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 72 publications
1
62
0
Order By: Relevance
“…Metallopolymers made by coordinating mono/multi‐dentate organic ditopic ligand with transition metal ion have recently expanded interest in material and supramolecular chemistry 1,2 . In these polymers, the organic structure is bonded to a metal ion with coordination bonds as well as a covalent bond through the complexation process 3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallopolymers made by coordinating mono/multi‐dentate organic ditopic ligand with transition metal ion have recently expanded interest in material and supramolecular chemistry 1,2 . In these polymers, the organic structure is bonded to a metal ion with coordination bonds as well as a covalent bond through the complexation process 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Metallopolymers made by coordinating mono/multidentate organic ditopic ligand with transition metal ion have recently expanded interest in material and supramolecular chemistry. 1,2 In these polymers, the organic structure is bonded to a metal ion with coordination bonds as well as a covalent bond through the complexation process. 3,4 So, the properties of the metallopolymers can be tuned by tuning the functional group in the organic structure and the change in metal ion in the inorganic part, which changes the electronic, magnetic, and optical properties of functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the specific, definite, and directional host−guest interactions, heteroditopic monomers has become one of the classic models as building blocks in self-assembly investigation. Driven by the unique multiple CH•••π interactions between the pillar [5]arene cavity and the linear n-alkyl group, copillar [5]arenes have become one of the simplest and optimal models for the construction of heteroditopic monomers in recent years. Here, by comparison of the reported crystal structures of heteroditopic copillar [5]arenes with six new ones (P6Br, P8Br, P6Im, P10Im, P4 ⊃ acetonnitrile, and P8Br ⊃ succinonitrile), we found that their self-assembly manner in the solid state was primarily decided by the competition of the pillar [5]arene cavity between the threading guest moiety and the solvent molecules (or external competitors).…”
mentioning
confidence: 99%
“…Since we have already known that P10Br (Figure S7) could spontaneously self-assemble as [c2]daisy chains in the solid state. 50 We first focused on the crystal structures of (P8Br, P6Br, and P4Br) to find out the influence of the linker length on the self-assembly manner of a heteroditopic copillar [5]arene with the same terminal group. After hundreds of attempts, we successfully got the single crystal structures of P8Br and P6Br.…”
mentioning
confidence: 99%
See 1 more Smart Citation